Origin of Topological Hall‐Like Feature in Epitaxial SrRuO3 Thin Films - Pinku Roy; Adra Carr; Tao Zhou; Binod Paudel; Xuejing Wang; Di Chen; Kyeong Tae Kang; Anastasios Pateras; Zachary Corey; Shizeng Lin; Jian‐Xin Zhu; Martin V. Holt; et al. (Advanced Electronic Materials, 2023)
Abstract The discovery of topological Hall effect (THE) has important implications for next‐generation high‐density nonvolatile memories, energy‐efficient nanoelectronics, and spintronic devices. Both real‐space topological spin configurations and two anomalous Hall effects (AHE) with opposite polarity due to two magnetic phases have been proposed for THE‐like feature in SrRuO3 (SRO) films. In this work, SRO thin films with and without THE‐like features are systematically Investigated to decipher the origin of the THE feature. Magnetic measurement reveals the coexistence of two magnetic phases of different coercivity (Hc) in both the films, but the hump feature cannot be explained by the two channel AHE model based on these two magnetic phases. In fact, the AHE is mainly governed by the magnetic phase with higher Hc. A diffusive Berry phase transition model is proposed to explain the THE feature. The coexistence of two Berry phases with opposite signs over a narrow temperature range in the high Hc magnetic phase can explain the THE like feature. Such a coexistence of two Berry phases is due to the strong local structural tilt and microstructure variation in the thinner films. This work provides an insight between structure/micro structure and THE like features in SRO epitaxial thin films.